COVID-19 associated Multisystem Inflammatory Syndrome in Children (MIS-C) guidelines; revisiting the Western New York approach as the pandemic evolves. (September 2021) - Hennon, Teresa R.; Yu, Karl O.A.; Penque, Michelle D.; Abdul-Aziz, Rabheh; Chang, Arthur C.; McGreevy, Megan B.; Pastore, John V.; Prout, Andrew J.; Schaefer, Beverly A.; Alibrahim, Omar S.; Gomez-Duarte, Oscar G.; Hicar, Mark D.
Abstract: Multisystem inflammatory syndrome of children (MIS-C) continues to be a highly concerning diagnosis in those recently infected with SARS-CoV-2. The diagnosis of MIS-C cases will likely become even more challenging as vaccine uptake and natural immunity in previously infected persons leads to lower circulating rates of SARS-CoV-2 infection and will make cases sporadic. Febrile children presenting with cardiac dysfunction, symptoms overlapping Kawasaki disease or significant gastrointestinal complaints warrant a thorough screen in emergency departments, urgent care centers, and outpatient pediatric or family medicine practices. An increased index of suspicion and discussion regarding higher level of care (transferring to pediatric tertiary care centers or to intensive care) continues to be recommended. Herein we outline a broad approach with a multidisciplinary team for those meeting the case definition and believe such an approach is crucial for successful outcomes. Highlights: MIS-C remains a diagnostic challenge; a multidisciplinary team approach continues to be recommended MIS-C should continue to be considered in febrile children until SARS-CoV-2 is no longer spreading MIS-C may present with significant cardiac and gastrointestinal symptoms, or symptoms overlapping Kawasaki disease Vaccine uptake and natural immunity likely will cause cases to appear sporadically Specific vaccination history may influence diagnostic test interpretation